1997
DOI: 10.1038/ng0197-62
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant cerebellar ataxia (SCA6) associated with small polyglutamine expansions in the α1A-voltage-dependent calcium channel

Abstract: A polymorphic CAG repeat was identified in the human alpha 1A voltage-dependent calcium channel subunit. To test the hypothesis that expansion of this CAG repeat could be the cause of an inherited progressive ataxia, we genotyped a large number of unrelated controls and ataxia patients. Eight unrelated patients with late onset ataxia had alleles with larger repeat numbers (21-27) compared to the number of repeats (4-16) in 475 non-ataxia individuals. Analysis of the repeat length in families of the affected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
997
8
8

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,510 publications
(1,044 citation statements)
references
References 40 publications
31
997
8
8
Order By: Relevance
“…Disorders not associated with FHM are episodic ataxia type 2 (Zafeiriou et al 2009, Cuenca-Leon et al 2009, Cricchi et al 2007, Jen et al 2004, 2008, Ophoff et al 1996, progressive ataxia (Yue et al 1997), spinocerebellar ataxia type 6 (Tsou et al , Restituito et al 2000, Ishikawa et al 1999, Zhuchenko et al 1997) and absence (Imbrici et al 2004) and generalized epilepsy (Haan et al 2005, Jouvenceau et al 2001). In addition FHM1 mutations were also found in family members who had only "normal" no-paretic migraine but no FHM.…”
Section: C2 Familial Hemiplegic Migraine Typementioning
confidence: 99%
“…Disorders not associated with FHM are episodic ataxia type 2 (Zafeiriou et al 2009, Cuenca-Leon et al 2009, Cricchi et al 2007, Jen et al 2004, 2008, Ophoff et al 1996, progressive ataxia (Yue et al 1997), spinocerebellar ataxia type 6 (Tsou et al , Restituito et al 2000, Ishikawa et al 1999, Zhuchenko et al 1997) and absence (Imbrici et al 2004) and generalized epilepsy (Haan et al 2005, Jouvenceau et al 2001). In addition FHM1 mutations were also found in family members who had only "normal" no-paretic migraine but no FHM.…”
Section: C2 Familial Hemiplegic Migraine Typementioning
confidence: 99%
“…In humans, mutations in the CACNA1A gene cause, in addition to FHM1, a few autosomal dominant neurological disorders characterized by cerebellar dysfunction, such as episodic ataxia type 2 (that may be associated with absence epilepsy in a few cases) and spinocerebellar ataxia type 6 9,26,27 (compare, Strupp 28 and Gomez 29 31,35,37,38 Recently, the generation of knockin mice carrying two different FHM1 mutations (R192Q and S218L) allowed the first analysis of mutant channels expressed at their endogenous level in neurons. [39][40][41] The studies in heterologous expression systems showed that the FHM1 mutations alter many biophysical properties of human Ca V 2.1 channels, in a complex way.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Expansion of polyglutamine repeats is associated with a toxic gain-of-function that affects specific neuronal populations in each of these diseases. 12 Huntington's disease (HD), one of the most extensively studied of these diseases, is a debilitating inherited neurodegenerative disorder characterized by involuntary movements, personality changes, dementia, and early death.…”
Section: Introductionmentioning
confidence: 99%